Pengaruh Suhu Permukaan Terhadap Kekerasan Kampas Rem Original Equipment Sparepart - Andretti, Jenson; Widiyarta, I Made; Parwata, I Made (Teknik Desain Mekanika; Vol 13 No 2 (2024): April 2024 : Teknik Desain Mekanik, 2024)
Abstract Break Pad is one of the important brake components because the break pads grips the disk brake thereby slowing down the speed of the vehicle. The Speed of the vehicle affects the braking load which has an impact on the wear of the brake pad material. The braking load affects the surface temperature of the brake lining which can change the hardness properties of the brake pad. Therefore, in this research, the writer carried out material hardness testing / Brinell Test. The results of research from material hardness testing / Brinnel Test with standards (ASTM E10-15) show that the indentation width increases along with increasing brake pad surface temperature, at room temperature 27 oC it has an HBW value of 56.74 HBW and consecutive research for temperature surfaces of 150, 250, 350, and 450 oC produce hardness values of 42.01 HBW, 36.33 HBW, 31.12 HBW, and 27.34 HBW, respectively. So can be concluded that surface temperature on the OES brake pad can affect the hardness of OES brake pad material. Keyword: Break pad, Surface Temperature, Brinell Test